PERAN CAMAT DALAM PELAKSANAAN KEGIATAN PEMERINTAHAN DI KECAMATAN ONOHAZUMBA NIAS SELATAN - Arman Sahabat Waruwu; Madin Silalahi (JURNAL GOVERNANCE OPINION, 2020)
This study aims at determining the role of the Camat (district head) in carrying out his duties and functions related to the implementation of community empowerment in villages in Onohazumba Subdistrict, South Nias Regency and explaining the factors that influence the implementation of the Camat's role in providing direction and orders to its staff regarding empowerment programs in Onohazumba District. The research method is descriptive qualitative approach, so that the data collected is by interview, literature study and observation. The results obtained from the Camat's role in coordinating community empowerment activities are as follows, namely, the Camat has encouraged community participation at the time of counseling to farmer groups in Onohazumba District. The Camat has made intensive communication with his staff for the success of work programs and community empowerment activities in the District's work area. However, the community's response was still lacking in following empowerment carried out from the district